PENGARUH WORD OF MOUTH DAN ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION PADA ONLINE SHOP SHOPEE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Jurusan Manajemen Universitas Islam Malang) - Mohamad Hashfi Auzan; Agus Widarko (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
Abstract This study aims to determine the effect of word of mouth, electronic word of mouth on purchase intention. The population in this study were students of the economics and business faculties of the management department of Malang Islamic University. The sample in this study uses purposive sampling totaling 77 students. This analysis uses multiple regression models. The results of this study indicate that word of mouth (X1) partially has a significant effect on purchase intention with a value (sig 0,000). As well as electronic word of mouth (X2) partially have a significant effect on purchase intention with value (sig 0,042). With the value of determination (R2) 26,7% between the independent variable and the dependent variable. Keywords word of mouth, electronic word of mouth and purchase intention